Soil nutrient balance and performance of basmati rice under organic nutrient management - SAHA, ANURADHA; BHARTI, VIJAY; RAI, P. K. (Journal of Soil and Water Conservation, 2020)
A field experiment was carried out during kharif season on loamy soil at University of Agricultural Sciences and Technology-Jammu to evaluate different organic sources in basmati (Basmati-564) rice (Oryza sativa L.) viz. green manures (Sesbania sps) (GM), Wheat straw (WS), Neem cake (NC), Vermicompost (VC), Farm yard manure (FYM), Azotobacter, phosphate solubilising bacteria (PSB), Blue green algae (BGA) and Mustard cake (MC) with recommended fertilizer dose. Recommended fertilizer dose (RFD) of NPK exhibited its superiority by giving maximum values for all the yield-contributing characters, grain yield and profits. However, all the organic nutrient based treatments except neem cake @ 2.5 t ha-1, GM @ 5 t/ha + PSB @ 5 kg/ha and mustard cake @ 2.5 t/ha were significantly at par with recommended fertilizer dose (RFD) of NPK for all the yield-contributing characters, grain yield and straw yield. Uptake of N, P and K by rice grown with inorganic fertilizer ranged 29-51% higher for N, 22-53% higher for P and 22-53% higher for K as compared to organic nutrient management based treatments. Maximum available N (213 kg ha-1), maximum available P (17.0 kg ha-1) and maximum available K (125 kg ha-1) were recorded from the plots that received neem cake @ 2.5 t ha-1. Economically, RFD of NPK through inorganic fertilizer recorded highest net returns and benefit cost ratio but organic nutrient management through GM @ 5 t ha-1 + BGA @ 1.25 kg ha-1 + Azotobacter provided highest benefit cost ratio, additional returns and net incremental cost benefit ratio.